2020
DOI: 10.2460/ajvr.81.9.714
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of suture caliber on the tensile strength of tenorrhaphies in cadaveric canine tendons

Abstract: OBJECTIVE To evaluate the effect of suture caliber on the tensile strength of tenorrhaphies performed with a locking-loop technique in cadaveric canine tendons SAMPLE 60 superficial digital flexor tendons (SDFTs) from 30 cadaveric adult dogs. PROCEDURES Transverse tenotomy was performed, and SDFTs were repaired with a locking-loop technique and polypropylene suture of 5 randomly assigned calibers: size-0, 2-0, 3-0, 4-0, or 5-0 (n = 12 SDFTs/suture caliber). Tendon constructs were tested to failure. Yield, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Due to the protracted period of tendinous healing following surgery, the limb is often supported to offload the repair with the talocrural joint held in extension by application of casts, calcaneotibial screw placement, or transarticular external skeletal fixation, applied for a period of at least 6 weeks to protect the primary repair 3,19 . Factors shown to affect the way in which repaired constructs fail include the inherent strength and functional integrity of anastomosed tissues, core suture size, and the number of suture strands crossing the repair 20‐22 . In clinical cases, failure of the primary repair may occur due to suture breakage or suture pull‐through.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the protracted period of tendinous healing following surgery, the limb is often supported to offload the repair with the talocrural joint held in extension by application of casts, calcaneotibial screw placement, or transarticular external skeletal fixation, applied for a period of at least 6 weeks to protect the primary repair 3,19 . Factors shown to affect the way in which repaired constructs fail include the inherent strength and functional integrity of anastomosed tissues, core suture size, and the number of suture strands crossing the repair 20‐22 . In clinical cases, failure of the primary repair may occur due to suture breakage or suture pull‐through.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that that tendons repaired with ExDCrL were stronger than 3LP and TCiL. We hypothesize these observed findings relate to the suture patterns, as other extraneous confounding variables; tendon type, bite distance from the transection site, 44 suture material, 45 and suture size 46 which affects construct strength were controlled during testing.…”
Section: Discussionmentioning
confidence: 79%
“…50 It is plausible that if a larger suture was used for tenorrhaphy that different results may have been obtained. 46 The clinical application of these novel patterns in dogs requires further in vivo evaluation. Factors that were not examined as part of this experimental design include the effect of these novel patterns on the local tendinous blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 To date, knowledge regarding surgical factors and successful outcomes during human tendinous repair have been established in comparative animal studies. 14,16,19,32,43,44 In addition to the number of core suture strands crossing the repair, 44 the calibre of the core suture, 45,46 depth of core suture penetrance, 47 placement of an epitendinous suture, 40 depth of epitendinous placement 48 and increasing the distance of epitendinous suture bite placement from the transection site 48 have all been identified as important surgical factors regarding the repair. Sequential increases in each of these evaluated variables resulted in increased strength, stiffness and resistance of the repair to the development of gap formation.…”
Section: Introductionmentioning
confidence: 99%